Pengaruh Beban Kerja dan Quality of Work Life terhadap Kinerja Pegawai dengan Kompetensi sebagai Variabel Mediasi - Widodo Widodo; Muryati Muryati; Choirum Rindah Istiqaroh; Rahayu Puji Suci; Aji Suraji; Armanu Thoyib (Journal of Management and Creative Business, 2026)
Employee performance is a key factor in achieving organizational effectiveness, particularly in public service organizations undergoing digital transformation. This study aims to analyze the effects of workload and Quality of Work Life (QWL) on employee performance, with competence serving as a mediating variable at PT Jasa Raharja Regional Office of East Java. This study employed a quantitative explanatory approach using a census method involving all 133 permanent employees. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that workload has no significant direct effect on employee performance, whereas Quality of Work Life and competence positively and significantly influence employee performance. In addition, workload and Quality of Work Life significantly enhance employee competence. The mediation analysis demonstrates that competence fully mediates the relationship between workload and employee performance and partially mediates the relationship between Quality of Work Life and employee performance. These findings indicate that employee competence plays a strategic role in transforming work demands into improved performance while strengthening the positive contribution of organizational support. Therefore, organizations should integrate competence development with initiatives to improve Quality of Work Life in order to sustain employee performance during organizational transformation.